2017
DOI: 10.1038/s41551-017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Conformal phased surfaces for wireless powering of bioelectronic microdevices

Abstract: Wireless powering could enable the long-term operation of advanced bioelectronic devices within the human body. Although both enhanced powering depth and device miniaturization can be achieved by shaping the field pattern within the body, existing electromagnetic structures do not provide the spatial phase control required to synthesize such patterns. Here, we describe the design and operation of conformal electromagnetic structures, termed phased surfaces, that interface with non-planar body surfaces and opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(112 citation statements)
references
References 28 publications
1
111
0
Order By: Relevance
“…The stability and transfer efficiency depend on the field distribution of the electromagnetic waves and therefore the antenna design is critical to ensure preferential radiation direction alignment with the implantable devices. Nevertheless, heating issues, penetration depth, and appropriate antenna size are critical challenges to be overcome …”
Section: Energy Transfer Devices Utilize Sources From the Surroundingmentioning
confidence: 99%
“…The stability and transfer efficiency depend on the field distribution of the electromagnetic waves and therefore the antenna design is critical to ensure preferential radiation direction alignment with the implantable devices. Nevertheless, heating issues, penetration depth, and appropriate antenna size are critical challenges to be overcome …”
Section: Energy Transfer Devices Utilize Sources From the Surroundingmentioning
confidence: 99%
“…Energies 2019, 12, x FOR PEER REVIEW 3 of 16 has also been studied to use propagating fields in the electromagnetic mid-field regime for transferring power to the deeper tissue than conventional electromagnetic power transfer methods [24]. However, this method is also limited for the amount energy to be transferred and thus is not suitable for charging purpose.…”
Section: The Principle Of Electrocardiogram (Ecg)mentioning
confidence: 99%
“…The ECG is a record of the electrical activity of the device implantation location is limited since the difference in medium, such as different organs, have different acoustic impedances affecting the efficiency [23]. Metal patterning has also been studied to use propagating fields in the electromagnetic mid-field regime for transferring power to the deeper tissue than conventional electromagnetic power transfer methods [24]. However, this method is also limited for the amount energy to be transferred and thus is not suitable for charging purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations show that when operating with the safe power limits, RF-antennas must be placed on the surface of the brain or in very shallow regions to harvest sufficient power for neural stimulation. "Mid-field" techniques (Agrawal et al 2017), improve the RF coupling efficiency enabling deep operation, but because this approach operates at a fixed frequency, individually addressable motes have yet to be demonstrated. Other techniques for wireless power delivery discussed previously, such magnetic induction, also cannot achieve deep, miniature, multichannel stimulation.…”
Section: Me Devices Can Be Individually Addressed Based Their Resonanmentioning
confidence: 99%
“…Montgomery et al and Ho et al have shown that one can use the mouse body as an electromagnetic resonant cavity to effectively transfer energy to sub-wavelength scale devices implanted inside the animal (Montgomery et al 2015;Ho et al 2015). This "mid-field" technique has also been further developed to use conformal phase surfaces to activate devices implanted in larger animals (Agrawal et al 2017). This approach is particularly effective to drive tiny LEDs for optogenetic stimulation in mice.…”
Section: Introductionmentioning
confidence: 99%